Biological maturity and relative age effects in German age-group swimming - Staub, I.; Cramer, l.; Bieder, A.; Vogt, T. (German Journal of Exercise and Sport Research, 2024)
Relative age effects (RAE) refer to a skewed distribution with an overrepresentation of athletes born close to the selection date. The prevalence of RAE has been repeatedly demonstrated in youth swimming. Additionally, being more mature within an age group is associated with consistent selection advantages. The present study aims to determine (1) the prevalence and magnitude of RAE in youth swimming and (2) the relation to anthropometry and biological maturity status. The study included 650 swimmers (male n = 273, age 11.00 ± 1.27 years; female n = 377, age 11.00 ± 1.25 years). The dates of birth were split into four birth quartiles (Q). The maturity status was assessed using equations to estimate the age of peak height velocity (APHV). X2 tests and analysis of variance (ANOVA) were used for statistical analyses. The X2 tests have shown significant RAE with medium effect sizes (ES; p < 0.001, 0.18 < V < 0.20) for male and female athletes. Also, the results have shown significant RAE with medium effect sizes (ES; p < 0.001, 0.18 < V < 0.20). ANOVA has not revealed significant differences regarding body height, body mass, and APHV between the four birth quartiles for both sexes, except for body mass in female athletes (p = 0.037). The findings indicate that maturity status and anthropometry influence RAE in youth swimming. It can be assumed that relatively younger swimmers can counteract their disadvantage only by similar anthropometric and maturity-related characteristics to the relatively older swimmers, which significantly impacts talent identification and development of swimmers.